2023
DOI: 10.1126/sciadv.ade4186
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 methylation restricts PD-L1/PD-1 interactions to control cancer immune surveillance

Abstract: Immune checkpoint inhibitors targeting programmed cell death protein 1 (PD-1) or programmed cell death 1 ligand 1 (PD-L1) have enabled some patients with cancer to experience durable, complete treatment responses; however, reliable anti–PD-(L)1 treatment response biomarkers are lacking. Our research found that PD-L1 K162 was methylated by SETD7 and demethylated by LSD2. Furthermore, PD-L1 K162 methylation controlled the PD-1/PD-L1 interaction and obviously enhanced the suppression of T cell activity controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 68 publications
3
17
1
Order By: Relevance
“…It was discovered that NSCLC patients who exhibited resistance to anti-PD-L1 demonstrated decreased levels of LSD2 and PD-L1 expression, as well as increased PD-L1 K162 methylation and SETD7 expression. 87 These findings provide support for the presence of immunosuppression and evasion mechanisms in cancers characterized by PD-L1 hypermethylation. 87 Notably, Qing et al 89 observed that anti-PD-1 therapy did not enhance T cell inhibition of GC cells expressing PD-L1P146R, both in vitro and in vivo.…”
Section: Epigenetic Regulation On Immunotherapy Efficacymentioning
confidence: 54%
See 2 more Smart Citations
“…It was discovered that NSCLC patients who exhibited resistance to anti-PD-L1 demonstrated decreased levels of LSD2 and PD-L1 expression, as well as increased PD-L1 K162 methylation and SETD7 expression. 87 These findings provide support for the presence of immunosuppression and evasion mechanisms in cancers characterized by PD-L1 hypermethylation. 87 Notably, Qing et al 89 observed that anti-PD-1 therapy did not enhance T cell inhibition of GC cells expressing PD-L1P146R, both in vitro and in vivo.…”
Section: Epigenetic Regulation On Immunotherapy Efficacymentioning
confidence: 54%
“…87 These findings provide support for the presence of immunosuppression and evasion mechanisms in cancers characterized by PD-L1 hypermethylation. 87 Notably, Qing et al 89 observed that anti-PD-1 therapy did not enhance T cell inhibition of GC cells expressing PD-L1P146R, both in vitro and in vivo. Additionally, recent research has indicated that the PD-1/PD-L1 colocation scores possess a strong predictive value for the response to anti-PD-1/PD-L1 therapy.…”
Section: Epigenetic Regulation On Immunotherapy Efficacymentioning
confidence: 54%
See 1 more Smart Citation
“…The extracellular regions contain four glycosylation sites (N35, N192, N200, and N219) [ 18 ], while the IgC domains have five phosphorylation sites (S176, T180, S184, S195, and T210) [ 19 , 20 ]. The cytoplasmic tail includes an S-palmitoylation site at C272 [ 21 ], six methylation sites (K75, K89, K105, R113, K162, and R212) [ 22 ], and an acetylation site at K263 [ 23 ]. Moreover, recent studies have shown that the PD-L1 intracellular domain functions as an RNA binding protein [ 24 ] (Fig.…”
Section: Structures Of Pd-1/pd-l1 and Their Potential Sites Modulate ...mentioning
confidence: 99%
“…Normally, they can inhibit T cell activity by binding to PD-L1 or PD-L2 ligands on the surface of normal cells, preventing unintended damage to normal cells ( 86 ). However, tumor cells can evade immune response by bypassing the immune surveillance of T cells through upregulation of PD-L1 ( 83 , 87 ). In a study of axitinib-resistant ccRCC mice, ADAMTS18 may act as a similar immunosuppressor by reducing immune escape and enhancing anti-tumor immunity through the up-regulation of the ratio of CD8+ and CD4+ T cells as well as the down-regulation of the ratio of CD45+/PD-L1 ( 27 , 88 ).…”
Section: Adamts18 and Tumor Microenvironmentmentioning
confidence: 99%